Man, Engineering and Ethics - Cyril Diatka (Communications - Scientific letters of the University of Zilina, 2018)
In today’s technologically advanced and science-driven societies, a tension arises between the natural process of using our rationality that focuses more or less on the purpose and the practical questions of using new pieces of knowledge that we have gained mostly through modern engineering and technologies. There is often a significant contradiction between that which the required changes should bring about and that which they bring about in reality. The fact here is that the social reality since we are present in it not only with our rationality but also with our desires and ideas often changes the acquired pieces of knowledge and their utilization in such a way that their impact in social reality can be and even become undesirable. The thoughts of some representatives such as e.g. the culture critic Hans Jonas or the social thinker G. Lipovetsky can serve as a starting point, whereby already some authors in the past, such as Erich Fromm in his work “To Have or to Be”, point out this reality and offer a viable alternative that ultimately proves to be more satisfying to human individuals and societies.